Experimental verification of the effectiveness of the structural-organizational model of training future economists by means of ICT - Dudka, U (Problems of Engineer-Pedagogical Education, 2019)
The problem of training economics specialists for professional activities by means of information and communication technologies is discussed in the article. The generalization of theoretical concepts for determining the content and structure of readiness allowed us to formulate a definition of readiness for the professional activities of future economists by means of information and communication technologies. This readiness has a system structure and is viewed as an aggregate, interaction and interpenetration of personality-motivational, informative, and operational components. The organizational and pedagogical conditions that ensure the formation of readiness for professional activities of future economists by means of ICT in agrotechnical colleges are substantiated with regard toscholarly works of domestic scientists (usingcomputer-oriented forms and methods of organizing education, enhancing cognitive activity by means of ICT, organizing distance learning based on the Moodle system as a component of computer-oriented education of future economists). The article also considers the implementation of these conditions in process of training future economists in colleges and describesthe designed structural-organizational model for training future economists by means of ICT in agrotechnical colleges. The model comprises targeted, conceptual, organizational-technological, and resultant blocks. Criteria and levels for assessing the readiness of future economists for professional activity by means of information and communication technologies are highlighted. In order to verify the effectiveness of the proposed model and conditions, an experimental study was conducted. The pedagogical experiment was carried out in several stages (ascertaining, searching, forming, and generalizing). The article describes the diagnostic measures to check the preparedness for professional activity according to the criteria and levels selected before and after the implementation of the organizational and pedagogical conditions. The generalized results of the experiment are presented in the paper. Conclusions on the effectiveness of the proposed model and organizational and pedagogical conditions are made.